Apakah Perilaku Kewarganegaraan Organisasi Dan Komitmen Afektif Berperan Dalam Kesiapan Karyawan Untuk Berubah? - Amelya Desvina; Onan Marakali Siregar (Owner : Riset dan Jurnal Akuntansi, 2022)
Changes in digitization at Tirtanadi Regional Water Company Medan (PDAM Tirtanadi) as a form of the organization's efforts to overcome the problem of offline services. The importance of employee readiness to change PDAM Tirtanadi Medan will support the planned transformation as expected. This study aimed to determine the effect of organizational citizenship behavior (OCB) and affective commitment on employee readiness to change at PDAM Tirtanadi Medan. This study used quantitative methods involving 88 employees as research samples. The sampling technique was simple random sampling. The data collection used was a questionnaire using a Likert scale which was distributed to respondents via a google form. The data analysis technique used an instrument test of reliability validity, classical assumption test, and hypothesis test was done by using multiple linear regression analysis. The results of this study indicate that OCB and affective commitment have a significant effect on employee readiness to change at the PDAM Tirtanadi Medan partially and simultaneously. The effect is given by OCB and affective commitment contributed to employee readiness to change, which is amounting to 14.6%. In this case, it is necessary to increase OCB and affective commitment that is right on target so that it can continue to improve employee readiness for the better. So that the increase in company productivity will also increase